2012
DOI: 10.7314/apjcp.2012.13.8.3899
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of B7-H3 in Colonic Carcinoma Cells

Abstract: B7-H3 is a newly discovered member of the B7/CD28 superfamily which functions as an important T-cell immune molecule. It has been reported recently that B7-H3 is highly expressed in many cancer cells, the data indicating that it may be a regulation factor contributing to tumor-resistance. In our study, we used bioinformatics to identify differentially expressed genes between colonic cancer cells and normal colonic cells, aiming to analyze mechanisms and identify sub-pathways closely related to progression, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A good model system that mimics the disease in humans is necessary for performing research that assists in refining the knowledge in this field. Controversy exists with regard to the B7-H3 protein, with one debatable point being the different responses in the in vitro and in vivo study of various cancer types ( 25 ). Mice have a natural ability to form osteosarcoma spontaneously ( 26 ) and exhibit useful responses after triggering the disease condition artificially.…”
Section: Discussionmentioning
confidence: 99%
“…A good model system that mimics the disease in humans is necessary for performing research that assists in refining the knowledge in this field. Controversy exists with regard to the B7-H3 protein, with one debatable point being the different responses in the in vitro and in vivo study of various cancer types ( 25 ). Mice have a natural ability to form osteosarcoma spontaneously ( 26 ) and exhibit useful responses after triggering the disease condition artificially.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that B7-H3, which functioned at the plasma membrane, brought a critical activation to the lymphocyte, thus validating the findings by other groups on the immunological role of B7-H3 in T-cell response. In-depth studies into the biological pathways revealed that B7-H3 was involved in T-lymphocyte receptor signaling, leading to automatic immune resistance [ 18 ]. More details on T-cell regulation by B7-H3 in TME are described in Sect.…”
Section: B7-h3: An Overviewmentioning
confidence: 99%